Peran Kepala Madrasah dalam Membina Minat dan Daya Baca Siswa Melalui Program Literasi Semesa - Hidayah, Nur; Fauyan, Muchamad (Indonesian Journal of Islamic Elementary Education, 2021)
The head of madrasah has a very strategic role in the success of the program in madrasah. The change of leadership at MI Walisongo Podo is a turning point in the program of fostering student interest and reading ability. The principal of Madrasah MI Walisongo Podo used his managerial role to initiate the Monday Reading Together (SEMESA) literacy program which was supported by all madrasa citizens. The research method used is field research with a descriptive qualitative approach. Data collection techniques are carried out by observation, interviews, and documentation. The data obtained were then analyzed using the Miles and Huberman analysis technique with the stages of data reduction, data presentation, and conclusion drawing. The results of this study indicate a vital role as a madrasa principal in fostering reading interest through the SEMESA literacy program at MI Walisongo Podo. The role of the headmaster at MI Walisongo Podo is in line with Henry Mintzberg's theory that every leader, wherever the hierarchy is located, is described in 3 main roles and detailed in ten roles: (1) the role of interpersonal relationships (Interpersonal), consisting of three roles, among others: ( a) a representative / symbolic role, (b) a leader role, (c) a liaison role; (2) the role of connecting information, consisting of three roles, among others: (a) the role of monitoring the flow of information, (b) forwarding information, (c) spokesperson; and (3) the role of the decision maker, which consists of four roles, including: (a) entrepreneur / pioneer, (b) alleviation of constraints, (c) allocator of my resources, and (d) negotiation. The ability of the madrasah principal to innovate and collaborate with all parties is a way out in maximizing supporting factors and minimizing inhibiting factors.